PENTINGNYA KEWIRAUSAHAAN DAN PROPOSAL CANVAS UNTUK WIRAUSAHAWAN MUDA - Novawiguna Kemalasari; Nengzih, Nengzih (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Entrepreneurship not only creates job opportunities for individuals but also fosters creativity and innovation. According to research conducted by the Global Entrepreneurship Monitor (GEM) in 2024, approximately 27% of the youth in Indonesia express an interest in starting their own businesses (GEM, 2024). This statistic indicates a strong entrepreneurial spirit among young people. By leveraging technology and social media, they can access a broader market and introduce innovative products or services. This community service activity aims to increase the capacity of the community, especially young people, in managing the MSMEs that have been run. The training was carried out directly on the Mercu Buana University campus and was held via Google Meet on April 29, 2025 and April 30, 2025 with 100 participants from the Young MSMEs of Kembangan District, West Jakarta. The training methods include material presentation, discussion, and direct practice, covering topics such as making natural soap, making fruit noodles, business proposals using the canvas method. The evaluation results showed that 90% of participants were satisfied with the material presented and considered this training useful for improving information and quality in running their MSMEs. The implications of this activity include providing a choice of renewable product innovations, proposal quality to attract investors, improving family financial well-being, resilience in the face of economic shocks, contributing to broader economic stability. Similar activities need to be continuously carried out and developed to provide a broader positive impact on society and the Indonesian economy